Helpful or harmful? How cancer beliefs and information seeking relate to depression in U.S. adults - Ama Gyesiwaa Quansah; Helena Baffoe; Solomon Eshun (PLoS ONE, 2026)
This study examined how cancer-related beliefs, information-seeking behaviors, and discussions about health with family or friends relate to depressive symptoms (PHQ-2 ≥ 3) among U.S. adults, using data from the 2024 Health Information National Trends Survey (HINTS 7; unweighted N = 6,826). Associations were estimated using survey-weighted logistic regression with jackknife replicate weights, adjusting for sociodemographic factors and personal or family cancer history; results are reported as adjusted odds ratios (ORs) with 95% confidence intervals (CIs). Weighted estimates indicate that approximately 15.5% of respondents screened positive for depression. Fatalistic beliefs, particularly the views that everything causes cancer (OR = 1.86; 95% CI: 1.39–2.48), prevention is not possible (OR = 1.69; 95% CI: 1.25–2.28), and cancer automatically means death (OR = 1.75; 95% CI: 1.31–2.34), were significantly associated with higher odds of screening positive for depression. In contrast, neither cancer information seeking (OR = 1.12; 95% CI: 0.83–1.51) nor discussions about health with family or friends (OR = 0.90; 95% CI: 0.62–1.30) showed a significant independent association with depression. In moderation analyses, discussions about health with family or friends weakened the positive association between each fatalistic belief and depression, but these interaction effects were not statistically significant. Sensitivity analyses using multiple imputation for missing data and restricting the analyses to respondents without a personal cancer history produced consistent results. Theoretical and practical implications of these findings are discussed.